Introduction of principles of blood management to healthy donor bone marrow harvesting. Issue 8 (7th July 2020) - Kim‐Wanner, Soo‐Zin; Luxembourg, Beate; Schmidt, Alexander H.; Schäfer, Richard; Möller, Nadine; Herbert, Eva; Poppe, Carolin; Hümmer, Christiane; Bunos, Milica; Seifried, Erhard; Bonig, Halvard
Abstract : Background and Objectives: Patient blood (more accurately: haemoglobin, Hb) management (PBM) aims to optimize endogenous Hb production and to minimize iatrogenic Hb loss while maintaining patient safety and optimal effectiveness of medical interventions. PBM was adopted as policy for patients by the World Health Organization (WHO), and, all the more, should be applied to healthy donors. Materials and Methods: Observational data from 489 bone marrow (BM) donors were retrospectively analysed, and principles of patient blood management were applied to healthy volunteer BM donations. Results and Conclusion: We managed to render BM aspiration safe for donors, notably completely avoiding the collection of autologous blood units and blood transfusions through iron management, establishment and curation of high‐yield aspiration technique, limitation of collection volume to 1·5% of donor body weight and development of volume prediction algorithms for the requested cell dose.